An evaluation of nutrition, culinary, and production interventions using African indigenous vegetables on nutrition security among smallholder farmers in Western Kenya - Merchant, Emily V.; Odendo, Martins; Maiyo, Norah; Govindasamy, Ramu; Morin, Xenia K.; Simon, James E.; Hoffman, Daniel J. (Frontiers in Nutrition, 2023)
Food security continues to worsen in sub-Saharan Africa. African Indigenous Vegetables (AIVs) are yet to be fully exploited to achieve food and nutrition security. The objective of this study was to evaluate the programmatic impact of AIV interventions on food and nutrition security. Smallholder farmers (18 to 65 years) from five counties in Western Kenya were randomly assigned to one of four treatments: 1. control; 2. production intervention (PI); 3. nutrition and culinary intervention (NCI); and 4. NCI/PI. Quantitative baseline and endline surveys were administered in October 2016 and June to July 2019, respectively. The impact evaluation was analyzed by Household Hunger Scale (HHS), Women’s Dietary Diversity Score (WDDS), AIV consumption frequency, and AIV market availability. Results showed that seasonal differences resulted in an overall decrease in WDDS, HHS, and consumption frequency between baseline and endline. Despite this, post-intervention, households that received NCI/PI demonstrated a protective effect as measured by a higher WDDS relative to the control: WDDS 5.1 ± 1.8 vs 4.2 ± 1.5, p = 0.035. In addition, between baseline and endline, there was an overall increase in the percentage of respondents that reported an adequate supply of key AIVs, particularly for households that received PI. Furthermore, seasonal effects caused a reported shift in the primary location for purchasing AIVs from the village to the town market. While ‘diet awareness’ significantly influenced diet quality among the NCI treatment group, ‘production’ was reported to have the greatest influence on diet quality among all intervention groups. Nutrition and culinary interventions, particularly when coupled with production interventions, provided a protective effect against the seasonal decline of availability and subsequent consumption of AIVs. Applications of such interventions have the potential to improve food security in rural Kenya.